Mekanisme Dan Regulasi Penegakan Hukum Terhadap Streamer Game yang Menyampaikan Informasi Tentang Judi Online - Pirnando, Yosepto; Kusnadi, Yopi; Angkupi, Prima (Universitas Muhammadiyah Metro, 2024)
Individuals who promote online gambling platforms to online media because they also support the occurrence of online gambling, This research explores law enforcement against individuals who disseminate gambling information through online media which will discuss related to legal basis, enforcement procedures, forms of law enforcement, influencing factors and problem solving mechanisms. The research aims to understand the mechanisms and procedures of law enforcement, the form of law enforcement, and the influencing factors. The results of the study show that there are still shortcomings in the government's efforts to prevent this problem and inequality in law enforcement.